Effects of Interpretive Guiding Outcomes on Tourist Satisfaction and Behavioral Intention. (May 2015) - Huang, Songshan (Sam); Weiler, Betty; Assaker, Guy
This study examined the effects of both cognitive and affective tour guide interpretation outcomes on tourist satisfaction and behavioral intention in a heritage tourism context. Data were collected via a survey of 282 inbound mainland Chinese tourists to Sovereign Hill, Ballarat, a heritage tourism site in Victoria, Australia. A hierarchical structural model was constructed based on a comprehensive literature review of tour guiding, interpretation, and tourist satisfaction and was tested applying partial least squares structural equation modeling. Results show that cognitive interpretation outcome has a greater impact on tourist satisfaction and sustaining visitor arrivals than affective interpretation outcome, whereas satisfaction with the guided tour experience directly affects behavioral intention and largely mediates the effect of cognitive interpretation outcome on behavioral intention. The study offers both theoretical insights in relation to interpretation and tourist satisfaction and practical implications for interpretive tour guiding.